Local Economic Impacts of Wind Power Deployment in Denmark - Claire Gavard; Jonas Göbel; Niklas Schoch (Environmental and Resource Economics, 2025)
An argument sometimes used to support renewable energy is that it may contribute to job creation. On the other hand, these technologies often face local opposition. In the case of Denmark, the country with the longest wind power experience, we examine whether the installation of new turbines had local economic benefits. Using the Danish master data register of wind turbines and detailed data on the municipal budget, personal income and sectoral employment from Statistics Denmark, we build a panel covering 250 municipalities. We use a quasi-experimental set-up and exploit time and regional variations at the municipal level. We find that the deployment of wind power contributed to the increase in personal income for entrepreneurs and reduced dependence on social benefits. As municipalities received payments from wind investors ahead of the construction, the new wind revenues were also followed by increases in local public spending. We find only very minor effects on employment in some sectors, and the aggregate local employment does not change significantly. Heterogeneity analyses indicate that the increases in local entrepreneurial income are largely driven by small installations, whilst increases in municipal budget and reductions in the dependence on social benefits are induced by larger installations.
Keywords: C23; H23; Q42; Q48; 330; Wind power; Renewable energy; Climate policy; Co-benefits; Employment